2010
DOI: 10.1108/00070701011052682
|View full text |Cite
|
Sign up to set email alerts
|

Information models leveraging identification of returnable transport items

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…To analyse traceability enabled by the implementation of the EPCIS standard and RFID technology, food supply chains were modelled as logistical chains consisting of links, traceability partners and events. A link connects two or several partners, representing either the physical movement or the information flow linked to a traceable resource unit (TRU) of goods (Senneset et al, 2010). Each link is set by the two main categories, external and internal traceability, which exist in food supply chains.…”
Section: Resultsmentioning
confidence: 99%
“…To analyse traceability enabled by the implementation of the EPCIS standard and RFID technology, food supply chains were modelled as logistical chains consisting of links, traceability partners and events. A link connects two or several partners, representing either the physical movement or the information flow linked to a traceable resource unit (TRU) of goods (Senneset et al, 2010). Each link is set by the two main categories, external and internal traceability, which exist in food supply chains.…”
Section: Resultsmentioning
confidence: 99%
“…It also obstructs counterfeited, contaminated or harmful products from reaching the market (Voss et al, 2009), and allows the causes of food safety deficiencies to be identified, hence limiting their impact (Thakur and Hurburgh, 2009). The definition of a traceable resource unit (TRU) is a key to successful unique identification (Manos and Manikas, 2010;Thakur and Hurburgh, 2009;Senneset et al, 2010;Karlsen et al, 2012). A TRU usually has homogenous content and product characteristics that may be priced, ordered, invoiced or included in production at any point in food SCs (Senneset et al, 2007;Regattieri et al, 2007;Thakur and Hurburgh, 2009).…”
Section: Unique Identification Of Goods Perspectivementioning
confidence: 99%
“…This paper provides theoretical contributions to at least three bodies of literature. First of all, the study contributes to the literature on BPM (Al-Mashari and Al-Mudimigh, 2003;Del Giudice and Della Peruta, 2016;Laurenza et al, 2018;Senneset et al, 2010;Trivelli et al, 2019) in particular to business process modeling (Weske, 2019), by promoting a shift from linear to systemic business process models in public administrations in order to effectively innovate their business processes (Bianchi, 2010;Lane et al, 2010;Leat and Setzler, 2002;Padua and Jabbour, 2015). The conceptual framework developed in this study allows public administrations to exercise their power by actively involving outside players and to increase their awareness about the social impact of their activities (Ashok et al, 2016;Hughes, 2010;Rundh, 2009).…”
Section: Discussionmentioning
confidence: 99%